ANALISIS PENGARUH LIKUIDITAS, LEVERAGE DAN AKTIVITAS TERHADAP RETURN ON EQUITY PADA PERUSAHAAN SUB – SEKTOR PERKEBUNAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2007 – 2012 - B11110006, MARDIANI (Jurnal Manajemen Update, 2015)
The objective of this study is to determine of the liquidity, Leverage and Activity effect on Return On Equity (ROE) on the agrriculture companies listed in Indonesia Stock Exchange. Sample in this research are Agriculture companies which is listed on Indonesia Stock Exchange, so the collected sample was 7 firms during 2007 – 2012 observation periode, the total of data that use is 42 with sampling technique use purposive sampling. This study used linier regression to see the contribution form each independent variables influenced Return On Equity (ROE). The result of  regression test shows that the liquidity, Leverage and Activity variables has significant influence to Return On Equity (ROE). The result which significant from this research show that Leverage and Activity variables also effect profitability of company. Keyword    :    The liquidity, The Leverage, The Activity, and Return On Equity (ROE)